Decentralization for improving the provision of public services in developing countries: A critical review - Christopher Dick-Sagoe (Cogent Economics & Finance, 2020)
Decentralisation, which sends power and resources from the Central to local governments, comes with several theoretical promises. One such promise is the improvement in local service provision. However, achieving these theoretical promises of decentralization has been a big challenge in most developing countries. This study aims to address the question "does decentralization improve service delivery levels at the local level, as promised?" This study reviews work on decentralization and service provision in developing countries and bring out some lessons from these works. To do this, the study falls on a set of articles from world-class scholars on decentralisation and service provision and key findings and themes from their works. As has been stressed in the conclusion, decentralisation has made some gains in meeting the real needs of local people in terms of service provision. In some instances, increases in the expenditure of local governments have increased service provision levels. However, the level of quality of these service providers through decentralisation has remained questionable. The author argues that an increase in service provision is good; however, it is the quality of these service provisions at the local level that can reduce poverty at the local level. The study, therefore, recommends for a revisit of the design of decentralisation to embrace the type which seeks to empower the local people to demand transparency and accountability from local government officials. With this, the effectiveness of administrative, fiscal and political decentralisation along with clear channels for local accountability and transparency are necessary for improved and quality service provision.
Keywords: 330; decentralisation; Ghana; local development; local government; service provision